Anti-trypanosomal activity and DNA fingerprinting of fifteen Euphorbia species using ISSR and SCoT markers - Seham S. El-Hawary; Nadia M. Lithy; Elham Amin; Sameh F. AbouZid; Rabab Mohammed (Beni-Suef University Journal of Basic and Applied Sciences, 2021)
Abstract Background Euphorbia is the largest genus in family Euphorbiaceae with a great biological and genetic diversity. The anti-trypanosomal activity of the crude extract of 15 Euphorbia species against Trypanosoma brucei brucei was carried out. Furthermore, DNA fingerprinting of the tested species using ISSR and SCoT markers was also investigated. Results The anti-trypanosomal activity of the 15 Euphorbia species revealed the highest activity of E. officinarum L. and E. milli Des Moul. against Trypanosoma brucei brucei with IC50 values < 10 μg/mL after 48- and 72-h incubation. Moreover, the assessment of the genetic diversity among the 15 tested species showed similar correlation coefficients of 0.76–0.98 which classified Euphorbia species into two main groups, one contained two species and the other contained 13 species. Conclusions Some Euphorbia species exhibited significant growth inhibitory activity toward Trypanosoma brucei strain TC221. Results also indicated the suitability of both markers for genetic fingerprinting of the tested Euphorbia species. To our knowledge, this is the first detailed comparison of the performance of two targeted DNA molecular markers (SCoT and ISSR) on the tested 15 Euphorbia species. The results guide future efficient use of these molecular markers in the genetic analysis of Euphorbia.